Optical limiting behavior of tungstate fluorophosphate glasses - Poirier, Gaël [UNESP]; De Araújo, Cid B.; Messaddeq, Younes [UNESP]; Ribeiro, Sidney J.L. [UNESP]; Poulain, Marcel (SPIE, the international society for optics and photonics, 2003)
Nonlinear absorption measurements were performed on fluorophosphate glasses with high concentration of tungsten oxide. Large two-photon absorption coefficients, α2, were determined at 660 nm using nanosecond laser pulses. It was observed that α2 increases for increasing tungsten oxide concentrations and therefore the optical limiting performance of this new glass composition can be controlled.
Keywords: Chemical bonds; Dye lasers; Laser beams; Light absorption; Nonlinear optics; Phosphates; Photons; Tungsten compounds; Absorption coefficients; Fluorophosphate glasses; Optical limiting (OL) materials; Optical transients; Optical glass